Determinan Kejadian Pneumonia pada Balita (0-59) Bulan di Provinsi Jawa barat Tahun 2023 (Analisis Data SKI 2023) - Sri Rezeki; Evy Wisudariani; Hendra Dhermawan Sitanggang; Helmi Suryani Nasution; Adelina Fitri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Pneumonia is a leading cause of morbidity and mortality among children under five worldwide. In West Java Province, ist prevalence among children has increased, reachhing 15.2% in 2023. This study aims to identify factors associated with pneumonia incidence among children under five in West Java 2023. This study is a quantitative cross-sectional design using secondary data from SKI 2023, with a total sample of 5,060 respondents selected through total sampling. Data analysis was using STATA, including univariate, bivariate using chi-square test, and multivariate using Poisson Regression. The prevalence of pneumonia among children under five was 1.71%. significant associated factors were sex (p=0.023; PR=1.79; 95% CI: 1.08-2.96) and socioeconomic status (p=0.025; PR=0.36; 95% CI: 0.15-0.87). Non-significant factors include age, exclusive breastfeeding, nutritional status, birth weight, immunization status, vitamin A supplementation, floor and wall types, mosquito repellent use, household smoking, and maternal education. Sex was identified as the dominant factor after controlling for nutritional status, maternal education, and socioeconomic status. Special attention is needed for male toddlers to enhance immunity through limited outdoor playtime, healthy diets, complete immunization, and improved environmental hygiene.